Implementation of Waterfall Method in Model Development to Improve Learning Quality of Computer Network Courses - Sallu, Sulfikar; Harsono, Yhonanda; Fajarianto, Otto (JTP - Jurnal Teknologi Pendidikan, 2023)
This research aims to improve the learning quality of Computer Network course through the implementation of Waterfall method in the development of learning model. Waterfall method, with its focus on systematic and sequential approach in software development, is adapted to design and implement effective learning structure. This study uses qualitative research design with data collection through observation, interview, and documentation. Data analysis was conducted using content analysis method to evaluate the effectiveness of Waterfall-based learning model implementation. The results show that the implementation of Waterfall method facilitates structured planning, systematic development of learning materials, and continuous evaluation, which overall contribute to the improvement of learning quality. The developed learning model encourages students' active participation and improves the understanding of key concepts in Computer Networking. This research confirms that the Waterfall method can be effectively used outside the context of software development, particularly in improving the quality of learning in the academic field.